CFD study of heat transfer enhancement and fluid flow characteristics of laminar flow through tube with helical screw tape insert. (February 2019) - Tusar, Mehedi; Ahmed, Kazi; Bhuiya, Muhammad; Bhowmik, Palash; Rasul, Mohammad; Ashwath, Nanjappa
Abstract: In this study, a three-dimensional (3D) computational fluid dynamics (CFD) analysis is performed to investigate the heat transfer performance and fluid flow characteristics using a helical screw tape insert in pipe flow. An inserted tube geometry was improved using a helical coil i.e., wire-wrapped with 1.92 twist ratio. Single-phase, horizontal, and a laminar flow (200 < Re <2300) through an annular channel is considered. A flow domain is created first, and then discretized, later all boundary conditions are applied and finally, simulated it using ANSYS FLUENT. The results are analyzed and processed further to check for mesh sensitivity and experimental validation. The simulated results showed that the heat transfer rate in terms of Nusselt number increased 1.34-2.6 times, whereas, the friction factor also increased 3.5-8 times for wire-wrapped-tube i.e., the tube with helical screw tape insert in comparison to the plain tube. The thermal performance factor was evaluated and the maximum value is found 3.79 at a constant pumping power. The pressure drop was estimated which was increased due to the increased flow restriction by inserted coils.